Influence of Decadal Variability of Global Oceans on South Asian Monsoon and ENSO-Monsoon Relation - Krishnamurthy, Lakshmi (2012)
This study has investigated the influence of the decadal variability associated with global oceans on South Asian monsoon and El Niño-Southern Oscillation (ENSO)- monsoon relation. The results are based on observational analysis using long records of monsoon rainfall and circulation and coupled general circulation model experiments using the National Center for Atmospheric Research (NCAR) Community Climate System Model (CCSM) version 4 model. The multi-channel singular spectrum analysis (MSSA) of the observed rainfall over India yields three decadal modes. The first mode (52 year period) is associated with the Atlantic Multidecadal Oscillation (AMO), the second one (21 year) with the Pacific Decadal Oscillation (PDO) and the third mode (13 year) with the Atlantic tripole. The existence of these decadal modes in the monsoon was also found in the control simulation of NCAR CCSM4. The regionally de-coupled model experiments performed to isolate the influence of North Pacific and North Atlantic also substantiate the above results. The relation between the decadal modes in the monsoon rainfall with the known decadal modes in global SST is examined. The PDO has significant negative correlation with the Indian Monsoon Rainfall (IMR). The mechanism for PDO-monsoon relation is hypothesized through the seasonal footprinting mechanism and further through Walker and Hadley circulations. The model results also confirm the negative correlation between PDO and IMR and the mechanism through which PDO influences monsoon. Both observational and model analysis show that droughts (floods) are more likely over India than floods (droughts) when ENSO and PDO are in their warm (cold) phase. This study emphasizes the importance of carefully distinguishing the different decadal modes in the SST in the North Atlantic Ocean as they have different impacts on the monsoon. The AMO exhibits significant positive correlation with the IMR while the Atlantic tripole has significant negative correlation with the IMR. The AMO influences the Indian ...